Language Ideologies in the Chinese Context Orientations to English as a Lingua Franca - Wang, Ying (Developments in English as a lingua franca ;, 2020)
This book explores language ideologies in China, which encounters the unprecedented global spread of English as a lingua franca, against the backdrop of globalisation where China emerges as a rapidly developing economy with vigorous promotion of Chinese around the world. The book addresses Chinese speakers' ideologies in relation to ELF and provides insights into non-native English speakers' engagement in the development of English in the future.